Differences in gut microbiota among patients with anastomotic leak following colorectal cancer surgery - Yan, Junfeng; Wang, Qiushuang; Li, Qiang; Lu, Jiatong; Tong, Qiang (Frontiers in Microbiology, 2025)
BackgroundAnastomotic leak (AL) continues to be one of the most severe complications following colorectal surgery, with its incidence showing little change over time. The causes of anastomotic leak are varied, and the precise underlying mechanisms remain elusive. However, there is a growing body of evidence indicating a significant association between the intestinal microbiota and the occurrence of anastomotic leak.MethodsThis study aimed to investigate the preoperative gut microbiota in patients who developed anastomotic leak (AL) following colorectal surgery. We collected preoperative fecal samples from both patients who developed anastomotic leak and those who did not for clinical research. Utilizing 16S Ribosomal RNA (16S rRNA) sequencing, we examined differences in gut microbiota of preoperative patients with colorectal cancer to identify bacterial species that may either mitigate or exacerbate the risk of anastomotic leak. Additionally, we preoperatively fed mice with Lactobacillus casei Zhang to demonstrate its protective effects against anastomotic leak.ResultsWe observed a significant increase in the diversity of intestinal microbiota in patients with anastomotic leak compared to those without. Specifically, the populations of Lachnospiraceae (p < 0.05), Bacteroidaceae (p < 0.01), and Fusobacteriaceae (p < 0.05) were markedly higher in patients with anastomotic leak, whereas Lactobacillaceae levels were comparatively lower (p < 0.05). Animal studies further supported these findings; mice preoperatively fed with Lactobacillus demonstrated a significantly reduced likelihood of developing anastomotic leak compared to those on a normal diet, with a statistical significance (P < 0.05).ConclusionThis study indicates that the presence of Lachnospiraceae, Bacteroidaceae, and Fusobacteriaceae in the intestinal microbiota may contribute to the development of anastomotic leak. Conversely, Lactobacillus appears to serve a protective role, potentially inhibiting this complication. Animal experiments further support these findings, demonstrating that preoperative supplementation with Lactobacillus may effectively prevent anastomotic leak. Our research may offer a novel preventive strategy for preoperative prevention of anastomotic leak.